2021
DOI: 10.3390/app112110470
|View full text |Cite
|
Sign up to set email alerts
|

Hydrates for Cold Storage: Formation Characteristics, Stability, and Promoters

Abstract: The potential of hydrates formed from R141b (CH3CCl2F), trimethylolethane (TME), and tetra-n-butylammonium bromide/tetra-n-butylammonium chloride (TBAB/TBAC) to be used as working substances for cold storage was investigated to provide a solution for unbalanced energy grids. In this study, the characteristics of hydrate formation, crystal morphology of hydrates, and the stability of hydrate in cyclic formation under 0.1 MPa and at 5 °C were carried out. It found that the ice had a positive effect on the hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Cold energy storage in hydrates is also perceived as a form of energy storage in hydrates; however, as mentioned in the first paragraph of the introduction, the scope of this review excludes the thermal based energy storage aspects. Several comprehensive reviews on cold energy storage in hydrates are found in literature. Readers can refer to them to gather insight and knowledge about the research progress in this domain. Before examining methane and hydrogen storage in hydrates, a brief introduction on gas hydrates, their structures, and other applications is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Cold energy storage in hydrates is also perceived as a form of energy storage in hydrates; however, as mentioned in the first paragraph of the introduction, the scope of this review excludes the thermal based energy storage aspects. Several comprehensive reviews on cold energy storage in hydrates are found in literature. Readers can refer to them to gather insight and knowledge about the research progress in this domain. Before examining methane and hydrogen storage in hydrates, a brief introduction on gas hydrates, their structures, and other applications is discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that CO 2 emissions are an important cause of global warming and climate change. , To mitigate global warming and reduce CO 2 emissions, the capture and storage of CO 2 from the atmosphere and industrial production has attracted global attention. , Hydrate-based CO 2 sequestration (HCS) is a hot topic in hydrate utilization research and is an effective method to reduce CO 2 emissions . In addition, gas hydrate technology has been applied to seawater desalination, mixed gas separation, , hydrate cooling storage, and CO 2 –CH 4 replacement. …”
Section: Introductionmentioning
confidence: 99%
“…) and a nongas hydrate (such as semi-clathrate hydrate TBAB, TBAAc, etc. ). A Gas hydrate, compared with a nongas hydrate, has a high cold storage density . However, it needs to provide a higher pressure to meet a suitable phase transition temperature, which limits its application.…”
Section: Introductionmentioning
confidence: 99%
“…11−13 A Gas hydrate, compared with a nongas hydrate, has a high cold storage density. 14 However, it needs to provide a higher pressure to meet a suitable phase transition temperature, which limits its application. Some studies have pointed out that thermodynamic additives can be used to alleviate the harsh phase equilibrium condition of a gas hydrate, thus, making it close to a region of low pressure and high temperature.…”
Section: Introductionmentioning
confidence: 99%